Cerebral Arteriovenous Malformations: Evaluation and Management. (15th October 2014) - Ajiboye, Norman; Chalouhi, Nohra; Starke, Robert M.; Zanaty, Mario; Bell, Rodney
Abstract : There has been increased detection of incidental AVMs as result of the frequent use of advanced imaging techniques. The natural history of AVM is poorly understood and its management is controversial. This review provides an overview of the epidemiology, pathophysiology, natural history, clinical presentation, diagnosis, and management of AVMs. The authors discussed the imaging techniques available for detecting AVMs with regard to the advantages and disadvantages of each imaging modality. Furthermore, this review paper discusses the factors that must be considered for the most appropriate management strategy (based on the current evidence in the literature) and the risks and benefits of each management option.